Discriminating and mapping rice ecosystems in Central Luzon, Philippines using ENVISAT ASAR images - Obico, Mary Rose O. (2012)
Monitoring rice crop systems in the Philippines is essential in ensuring food security for the country. ENVISAT ASAR images offer an effective alternative to conventional methods of rice monitoring because of its all-weather imagine capability. This study determine the suitable approach in mapping irrigated and rainfed rice areas using multi-temporal ENVISAT ASAR images for two cropping seasons in Central Luzon with the purpose of updating land-use paper maps and to promote transfer of location-specific technologies, farm management, and cropping system. Five ASAR Alternating Polarization Precision (APP) images and eleven ASAR Image Mode (IM) images were acquired during the 2010 dry cropping season (JAnuary 1, February 5, and April 16) and 2010 wet cropping season (May 23, June 11, June 27, August 1, August 20, and September 5), respectively. Image pre-processing and calculation of radar backscatter coefficient of the images were performed. Supervised classification techniques were applied to the colour composite images. Rice area estimation, accuracy assessment, and comparison of rice area produced from the classified images with the government reported statistics were also conducted.